Connected Subspecialty Care: Applying Telehealth Strategies to Specific Referral Barriers - Ray, Kristin N (Acad Pediatr, 2019)
Nearly a quarter of families of children with need of subspecialty care report difficulty accessing that care. Telehealth is a method to overcome barriers to subspecialty care. However, improving access to subspecialty care through telehealth requires granular identification of specific subspecialty barriers and recognition of the strengths and limitations of each telehealth strategy for addressing identified barriers. Focusing on each sequential step in subspecialty referrals and potential associated barriers, we summarize specific telehealth and technology-enabled strategies to improve access to subspecialty care, including electronic consultations, live interactive telemedicine, store-and-forward telemedicine, tele-mentoring, patient portals, and remote patient monitoring. Intentionally selecting telehealth strategies to target specific subspecialty referral barriers may avoid risks from misapplication of telehealth, may more clearly elevate equitable access as an essential goal within telehealth initiatives, and may also lead to synergistic use of strategies that overcome sequential barriers.